IMPLEMENTASI E-COMMERCE UNTUK MENINGKATKAN PEMASARAN ANYAMAN BAMBU DI METRO - Muhammad Said Hasibuan; Ridho Kurniawan (TECHSI - Jurnal Teknik Informatika, 2014)
The bamboo craft creative industry is one of creative industry which is located in Metro. That creative industry has not had online system in information spreading process and selling produced product process. The spreading of information just only reach certain area or location, even though some of the industry have already sell the product outside Metro. Therefore, to expand the product trading, it is made the e-commerce design as the shopping service media for bamboo craft creative industry in Metro. The website design is aimed to overcome the marketing and selling product problems in bamboo craft creative industry in Metro which is limited by the place and time. The software development method which is used is Waterfall method. The data collecting uses observation method. The implementation from this Waterfall method is explained by using running system analysis, proposed system analysis, diagram context system, data flow diagram (DFD), table relation, database structure table, and interface design system. This website design uses PHP program. This e-commerce website has three user based on the access right therefore it can be used by customer (end user), the owner (bamboo craft creative industry), and the administrator (website management).